Pediatric neuroanesthesia. Issue 5 (October 2018) - Lamsal, Ritesh; Rath, Girija P.
Abstract : Purpose of review: Pediatric neuroanesthesia is a fascinating, yet challenging branch of anesthesia. This review highlights some of the recent insights into pediatric neuroanesthesia from the past 18 months. Recent findings: Although there are incontrovertible evidences in animals suggesting that prolonged exposure to general anesthesia causes long-term neurological impairment, the translational relevance of these findings in humans is debatable. Early surgery for pediatric drug-refractory epilepsy is supported by emerging literature, but poses unique perioperative problems for the treating neuroanesthesiologist. Similarly, minimizing intraoperative blood loss and blood transfusion concerns every anesthesiologist managing small children. The usefulness of tranexamic acid in children is further enhanced by some studies in spine surgeries. Some pertinent issues related to intraoperative neuromonitoring are also discussed in the text. Summary: There are several logistical and ethical problems of carrying out high-quality prospective studies in children but important findings on prevention of anesthetic neurotoxicity; minimizing intraoperative blood loss, intraoperative neurophysiological monitoring, examining optimal doses and choices of anesthetic agents in epilepsy surgery have been published recently.